A green inventory model for deteriorating items while producing overtime with nonlinear cost and stock dependent demand - Vinodini R; Ritha W (The Scientific Temper, 2025)
Carbon emission alludes to the release of greenhouse gases into the atmosphere and the land or water as a result of human activities. These emissions are cause of the climate change, biodiversity loss, global warming and the degradation of ecosystems which affects our human health and environment. To overcome this problem, this study presents a green inventory model for deteriorating items while producing overtime with nonlinear cost and stock dependent demand. In this paper, the Production process allows for overtime operations with the nonlinear costs and the demand is influenced by the inventory level. The mathematical formulation is designed to optimize inventory management and to develop an ecofriendly model for the deteriorating items. The model was extended with two new costs that are Opportunity cost and Emission cost. To evaluate this green inventory model a numerical example was examined. The results are discussed with different values of the variables. As the final outcome of this model, the gross cost was determined for environmental benefits.